Utility of a Precision Medicine Test in Elderly Adults with Symptoms Suggestive of Coronary Artery Disease. Issue 2 (6th December 2017) - Ladapo, Joseph A.; Budoff, Matthew J.; Sharp, David; Kuo, Jane Z.; Huang, Lin; Maniet, Bruce; Herman, Lee; Monane, Mark
Abstract : Background: Diagnosing obstructive coronary artery disease (CAD) is challenging in elderly adults, and current diagnostic approaches for CAD expose these individuals to risks from contrast dye and invasive procedures. Design: A Registry to Evaluate Patterns of Care Associated with the Use of Corus CAD in Real World Clinical Care Settings (PRESET; NCT01677156), pragmatic clinical trial. Setting: Community, 21 primary care practices. Participants: Of 566 stable, nonacute outpatients presenting with symptoms suggestive of obstructive CAD, the 176 who were aged 65 and older (median age 70, 61% female) were the current study participants. Intervention: Blood‐based precision medicine test, incorporating age, sex, and gene expression score (ASGES) to improve clinical decision‐making and quality of care. Measurements: Information on demographic characteristics, clinical factors, ASGES results (range 1–40; low (≤15), high (>15)), referral patterns to cardiology and advanced cardiac testing, and major adverse cardiac events (MACEs) was collected in a subgroup analysis of elderly adults in the PRESET Registry. Follow‐up was for 1 year after ASGES testing. Results: Median ASGES was 25, and 40 (23%) participants had a low score. Clinicians referred 12.5% of participants with a low ASGES and 49.3% with a high ASGES to cardiology or advanced cardiac testing (odds ratio for referral = 0.12, P < .001, adjusted for participants demographics and clinical covariates). Higher scores were associated with greater likelihood of posttest cardiac referral. At 1‐year follow‐up, the incidence of a MACE or revascularization was 10% (13/136) in the high ASGES group and 0% (0/40) in the low ASGES group ( P = .04). Conclusion: The ASGES test showed potential clinical utility in the evaluation of elderly outpatients with symptoms suggestive of obstructive CAD. Test use may reduce unnecessary referrals and the risk of procedure‐related complications in individuals with low ASGES, who are unlikely to benefit from further testing, while also identifying individuals who may benefit from further cardiac evaluation and management.